2022
DOI: 10.37934/arfmts.99.1.114122
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Treatment on Microhardness and Surface Roughness of Electroless Ni-YSZ Composite Coating

Abstract: The application of heat treatment was introduced in Ni-YSZ composite coating as the incorporation of ceramic YSZ in electroless nickel deposition is new and worth investigating. In this paper, the influence of heat treatment by varying the heating temperature and time on the electroless Ni-YSZ composite coating is investigated. The Ni-YSZ composite is deposited onto a high-speed steel substrate via electroless nickel co-deposition. YSZ powder of mixed sizes of micro- and nano-sized of the ratio of 1:1 is incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…The peaks were also sharper. This indicated that the crystalline nature of the sample was increasing [4].…”
Section: Phase Analysismentioning
confidence: 94%
See 2 more Smart Citations
“…The peaks were also sharper. This indicated that the crystalline nature of the sample was increasing [4].…”
Section: Phase Analysismentioning
confidence: 94%
“…It was observed that the diffraction line became sharper and narrower as the calcination temperature increased. The sharp and narrow peaks indicated the formation of larger crystallite [4]. The dominant monoclinic phase was due to the temperature which was still in the phase transformation threshold and it was expected as there was no addition of dopant in the zirconia [31].…”
Section: Phase Analysismentioning
confidence: 95%
See 1 more Smart Citation